Morphologic evidence of telocytes in human thyroid stromal tissue. Issue 8 (20th March 2022) - Rosa, Irene; Ibba‐Manneschi, Lidia; Guasti, Daniele; Perigli, Giuliano; Faussone‐Pellegrini, Maria‐Simonetta; Manetti, Mirko
Abstract: Despite the evidence accumulated over the past decade that telocytes (TCs) are a distinctive, though long neglected, cell entity of the stromal microenvironment of several organs of the human body, to date their localization in the endocrine glands remains almost unexplored. This study was therefore undertaken to examine the presence and characteristics of TCs in normal human thyroid stromal tissue through an integrated morphologic approach featuring light microscopy and ultrastructural analysis. TCs were first identified by immunohistochemistry that revealed the existence of an intricate network of CD34 + stromal cells spread throughout the thyroid interfollicular connective tissue. Double immunofluorescence allowed to clearly differentiate CD34 + stromal cells lacking CD31 immunoreactivity from neighbour CD31 + microvascular structures, and the evidence that these stromal cells coexpressed CD34 and platelet‐derived growth factor receptor α further strengthened their identification as TCs. Transmission electron microscopy confirmed the presence of stromal cells ultrastructurally identifiable as TCs projecting their characteristic cytoplasmic processes (i.e., telopodes) into the narrow interstitium between thyroid follicles and blood microvessels, where telopodes intimately surrounded the basement membrane of thyrocytes. Collectively, these morphologic findings provide the first comprehensive demonstration that TCs are main constituents of the human thyroid stroma and lay the necessary groundwork for further in‐depth studies aimed at clarifying their putative implications in glandular homeostasis and pathophysiology.